Conceptual Types of Movement in the Translations of Works (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the conceptual types of action in the translations of the works, the types related to the aspectual semantics of the verb within the predicate, were highlighted. Momentary, durative, delimitative types, which are the main indicators of temporal modification, were analyzed with examples. The theoretical possibilities of how the semantic meanings of verb endings in the English language change in relation to the semantics of the verb, that is, that these endings have morphological, syntactic and semantic limitations. Conducting aspectual semantics directly within the framework of field theory, conducting it from a comparative-typological and cognitive point of view, it is shown that verb semantics is comprehensive and rich with the help of various combinations.